PEDAGOGICAL OUTCOMES OF TEACHER–STUDENT COMMUNICATION AND POSSIBILITIES FOR PRACTICA APPLICATION - Mammadli, Konul; Kazimova, Shafa (Revista Gênero e Interdisciplinaridade, 2025)
The article analyzes the pedagogical outcomes of teacher–student communication from theoretical and practical perspectives. Based on the main principles of modern pedagogy and psychology, the study examines the impact of effective communication on students’ motivation, academic achievement, and social–emotional development. Communication models observed in traditional and digital learning environments are compared, and the role of empathy and emotional intelligence is emphasized. The findings show that democratic communication styles and mutual understanding improve the quality of teaching and strengthen cooperation between teachers and students.